The Constitutional Court’s Interpretations on the Exercise of Executive’s Authority and the Protection of People’s Rights and Liberties under Public Emergency Situations - Jirathitikankit, Nitikon (Journal of Thai Ombudsman, 2026)
As judicial organization established under the spirit of the Constitution that intended to be mechanism for overseeing the exercise of state’s authority and protecting rights and liberties, the Constitutional Court thus performed the role in safeguarding people’s rights and liberties from the exercise of executive’s authority under public emergency situations based on duties and powers provided in the Constitution. This article, based on documentary analysis, aimed at examining judgments of the Constitutional Court regarding the protection of rights and liberties under public emergency situations in order to analyze the interpretations of the Thai Constitutional Court regarding types of emergency situation, the exercise of the Executive’s authority and rights and liberties of people under public emergency situations. After searching for the related judgments of the Constitutional Court, whether it was a ruling or an order, it was found that the interpretations of the Constitutional Court regarding types of emergency situation, the exercise of the Executive’s authority and rights and liberties of people under public emergency situations illustrated two approaches of interpretation namely ‘duty-based approach’ which the Constitutional Court emphasized the utilization of special power based on law of public emergency by the Executive and ‘right-based approach’ which human rights was received more important by the Constitutional Court than the former one. Additionally, the analyzed interpretations also illustrated legal limitations regarding the rules, procedures, and conditions of Constitutional Court’s procedures that caused an ineffectiveness of the protection of right and liberties of people from the exercise of State’s power under emergency situations by the Constitutional Court. In order to perform the role as ‘the last resort’ in protecting rights and liberties in any circumstances in accordance with the spirit of the Constitution, the Constitutional Court, based on subjective aspect of individual Justice consisted in a panel, should adopt ‘right-based interpretation approach’ even there were some legal limitations regarding the rules, procedures, and conditions of the Constitutional Court’s procedures. Moreover, such legal limitations would be revised in order to provide feasible way for the Constitutional Court to protect people’s rights and liberties once the Court had to consider the case of constitutional review of any law or act under emergency situation that drastically violated rights and liberties.